GEOLOGY COURSES IN GREEK HIGH SCHOOLS: AN OVERVIEW AND PROPOSALS FOR THE FUTURE - Σκαρπέλης Ν.; Ασημακοπούλου Αικ.; Μιχαλοπούλου Κ. (Bulletin of the Geological Society of Greece, 2018)
An overview of the earth science courses in the curriculum in the greek high schools from 1899 to 1999 is given in the paper. It was based on detailed searching within files related to educational issues included in the Official Journal of the Greek Government. Although all segments of society can benefit by an enhanced awareness of earth sciences, severe cutbacks in geology education took place last years. It is proposed that the school program should be designed to include a geology course for students of the 3rd class of Gymnasium or the 1s t class of the Lyceum, comprising a series of talks and demonstrations on diverse themes related to the evolution of the earth, management of water and mineral and energy resources, natural hazards, the responsible use of the geosphere, the earth processes affecting evolution of life, the origin of human race and the preservation of natural monuments.